The cultural-spiritual harmfulness of the secularization of communication in the media - Tănăsescu, Eugen (Technium Social Sciences Journal, 2023)
Today’s society is experiencing an accelerated phenomenon of secularization due to communication through today’s media channels. Daily, the global village called Earth transmits billions of news, information, cultural and spiritual values beneficial to the cultural and spiritual condition of contemporary man. We propose to analyze the phenomenon of media secularization on contemporary society, but also the harmful cultural and spiritual effects that society feels because of the secularizing informational flow. We will show the origins of this phenomenon and how it affects society through atheism, occultism, syncretism, hedonism, perfectionism, and media narcissism.